2015
DOI: 10.1534/genetics.115.182725
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Genome-Wide Instability in Yeast Mutants Lacking RNase H Activity

Abstract: Two types of RNA:DNA associations can lead to genome instability: the formation of R-loops during transcription and the incorporation of ribonucleotide monophosphates (rNMPs) into DNA during replication. Both ribonuclease (RNase) H1 and RNase H2 degrade the RNA component of R-loops, whereas only RNase H2 can remove one or a few rNMPs from DNA. We performed highresolution mapping of mitotic recombination events throughout the yeast genome in diploid strains of Saccharomyces cerevisiae lacking RNase H1 (rnh1D), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 39 publications
8
70
1
Order By: Relevance
“…The conclusion that RNase H2, but not H1, carries the major load of protecting cells against large-scale LOH corroborates a previous study (4). Although our work and that of O'Connell and colleagues (4) concluded that this protection results from RNase H2's removing R-loops, a different study of RNase H2's activities by Conover and colleagues (5) suggested that this protection is afforded by RNase H2's ability to remove misincorporated nucleotides.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The conclusion that RNase H2, but not H1, carries the major load of protecting cells against large-scale LOH corroborates a previous study (4). Although our work and that of O'Connell and colleagues (4) concluded that this protection results from RNase H2's removing R-loops, a different study of RNase H2's activities by Conover and colleagues (5) suggested that this protection is afforded by RNase H2's ability to remove misincorporated nucleotides.…”
Section: Discussionsupporting
confidence: 90%
“…Although our work and that of O'Connell and colleagues (4) concluded that this protection results from RNase H2's removing R-loops, a different study of RNase H2's activities by Conover and colleagues (5) suggested that this protection is afforded by RNase H2's ability to remove misincorporated nucleotides. In fact, many studies have shown that misincorporated ribonucleotides can lead to DNA damage and mutation in a topoisomerase I-dependent manner (13)(14)(15)(16).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Because it takes about 25 divisions to form a colony from a single cell, the rates of alterations per cell division in the strains with low levels of DNA polymerase α and δ are about 0.6 and 0.3, respectively. By a similar calculation using the data of O'Connell et al (17), the rate of genetic alterations in wild-type cells is about 2.4 × 10 −3 per division. Thus, low levels of either DNA polymerase α or δ elevate genomic instability by about two orders of magnitude.…”
Section: Significancementioning
confidence: 89%
“…However, a number of observations support our hypothesis of R-loops as inhibitors of repair. Inactivation of RNase H2 (rnh201D) by itself leads to large increases of genomic hybrids and loss of heterozygosity compared to wild-type (Wahba et al, 2016;O'Connell et al, 2015). This result suggests that loss of RNase H2 generates elevated levels of DNA damage.…”
Section: Discussionmentioning
confidence: 99%